Pengendalian Kualitas Proses Produksi Komponen Automotive di Industri Manufaktur dengan Pendekatan Six Sigma - Supriyati, Supriyati; Widyatri, Hasyrani (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2024)
Indonesia's manufacturing sector, which accounts for 18.67% of GDP, faces major challenges in terms of innovation and poverty. PT. XYZ, which produces automotive components using the Injection process, needs to improve product quality to reduce defects in the front cover panel. This study aims to overcome these problems by improving the cooling system, controlling machine parameters, and maintaining material viscosity, while ensuring quality standards through regular maintenance and training. This study uses the DMAIC approach to analyze product quality. Starting with a Baseline to assess Overall Equipment Effectiveness (OEE) and quality ratios, variations in DPMO and quality factors were found. The Define phase identifies key defects, Measure shows improvements over time, Analyzes using Fault Tree Analysis to find solutions, Improves implementation of improvements, and Controls the incorporation of machine parameters to maintain consistency and quality. The research results show large variations in Quality Ratio and Availability, indicating the need to improve OEE which currently ranges from 82.80% to 92.60%. With a total annual production of 345,842 units and 20,538 defective units, the focus of improvements should be on engine and cooling system parameters. This research enriches understanding of product quality models and analysis.